2017
DOI: 10.5455/njppp.2017.7.0515011052017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bioaerosol exposure on respiratory health of saw-mill workers

Abstract: Background: Occupational environments with organic dust and bioaerosols pose danger to the respiratory health of the personnel of such environments. Respiratory health of the workers of saw-mills in relation to airborne bacterial and fungal concentrations has rarely been studied in India. Aims and Objectives: This study was, therefore, designed to assess and compare the pulmonary functions (PFs) of saw-mill workers with those of matching controls. The study also aimed at assessment of bioaerosol exposure in sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…The proposed occupational exposure limit (OEL) for spores is 1-10 5 spores/m 3 and values of TFC in this study fell within the limit. Sawane and Sawane [28] reported a mean of 72.26 x 10 3 CFU/m 3 for bacteria 65.91 x 10 3 CFU/m 3 for fungi in their work, which is close in range with this study. Tobin et al [15] reported TVC and TFC > 4162.99 CFU/m 3 .…”
Section: Prevalence Of Respiratory Symptoms Among the Sawmill Workerssupporting
confidence: 88%
“…The proposed occupational exposure limit (OEL) for spores is 1-10 5 spores/m 3 and values of TFC in this study fell within the limit. Sawane and Sawane [28] reported a mean of 72.26 x 10 3 CFU/m 3 for bacteria 65.91 x 10 3 CFU/m 3 for fungi in their work, which is close in range with this study. Tobin et al [15] reported TVC and TFC > 4162.99 CFU/m 3 .…”
Section: Prevalence Of Respiratory Symptoms Among the Sawmill Workerssupporting
confidence: 88%